The Influence of Teaching Skills on Students' Learning Interest in Class VII Social Studies SMP Negeri 13 Pematang Siantar - Tasya Nanda Siahaan; Rosma Simangunsong; Tumpal Manahara Siahaan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of Teacher Teaching Skills on Interest Student Learning in Class VII Social Sciences Subjects at SMP Negeri 13 Pematang Siantar. Type the research used is field research with the nature of quantitative research. Data collection techniques used are questionnaires, observation, interviews, and documentation. The data obtained is questionnaire data. Test instrument using The classical assumption test and hypothesis test used are the t partial test (T test), and test Coefficient of Determination. Results of inferential statistical analysis (Simple Linear Regression) obtained the statistical equation Y 24.670 + 0.367 X which can be interpreted that if the value there is an increase in the teacher's teaching skills by one unit, then the interest in learning will be increased by 0.367. Furthermore, to test the hypothesis using a partial test (t test) who get the results of the significance value for the effect of the independent variable (skills teaching) to the dependent variable (interest in learning) is 0.000 <0.005 and the value tcount 3.698 > ttable 2.008 so it can be concluded that there is an influence significant teacher's teaching skills on student learning interest in social studies subjects class VII SMP Negeri 13 Pematang Siantar.